1970
DOI: 10.15581/003.24.36214
|View full text |Cite
|
Sign up to set email alerts
|

Communication Policies and the Protection of Pluralism in the European Union and the United States

Abstract: This article describes and analyses the regulatory frameworks and the current pluralism protection policies in the United States and several countries of the European Union (Germany, France, the United Kingdom, the Netherlands, Italy and Spain). The data obtained allowed a qualitative assessment to be carried out, through a comparative analysis, in order to identify certain similarities and some significant differences. Thus, it was found that pluralism protection is a common denominator in the communication p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In total, 385 users started the second wave of the survey and 162 users successfully uploaded their browsing history (16 Safari,113 Chrome,18 Firefox,15 Edge). Of those, 100 indicated that they successfully synched their desktop and 61 Not all devices and browsers are compatible.…”
Section: Samplementioning
confidence: 99%
“…In total, 385 users started the second wave of the survey and 162 users successfully uploaded their browsing history (16 Safari,113 Chrome,18 Firefox,15 Edge). Of those, 100 indicated that they successfully synched their desktop and 61 Not all devices and browsers are compatible.…”
Section: Samplementioning
confidence: 99%